Legal Analysis of Money Politics in Elections under Law Number 7 of 2023 Amendments - Hasiholan, Maju; Yusuf Siregar, Muhammad; Hakim, Abdul (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
In the context of Indonesian elections, money politics has been a persistent issue that undermines the integrity and fairness of the electoral process. It involves the distribution of money or other material benefits to influence voters' choices, often leading to corrupt practices and a lack of public trust in the democratic system. The purpose of this research is to know and understand the Legal Arrangements regarding the Crime of Money Politics from the Perspective of Law Number 7 of 2023 concerning the Stipulation of Government Regulations instead of Law Number 1 of 2022 concerning Amendments to Law Number 7 of 2017 concerning General Elections into Law. This research uses normative law research, namely normative case studies in the form of legal behavior products, by examining the Law. The subject matter is law which is conceptualized as norms or rules that apply in society and become a reference for everyone's behavior. Discussion: Legal Regulations on the Crime of Money Politics in the Perspective of Law Number 7 of 2023 Concerning the Stipulation of Government Regulation instead of Law Number 1 of 2022 Concerning Amendments to Law Number 7 of 2017 Concerning General Elections into Law, among others: Articles 278, 280, 284, 515, and 523 of Law Number 7 Year 2017 on General Elections. Article 515 reads "Every person who intentionally at the time of voting promises or gives money or other material to the Voters so as not to exercise their voting rights or vote for certain Election Participants or exercise their voting rights in a certain way so that the ballots are invalid, shall be punished with a maximum imprisonment of 3 (three) years and a maximum fine of Rp. 36,000,000.00 (thirty-six million rupiah)".